Chloroplast Genomes for Five Skeletonema Species: Comparative and Phylogenetic Analysis - Liu, Shuya; Xu, Qing; Liu, Kuiyan; Zhao, Yongfang; Chen, Nansheng (Frontiers in Plant Science, 2021)
Skeletonema species are cosmopolitan coastal diatoms that exhibit important roles in ecological system. The chloroplast genomes (cpDNAs) have been proven to be important in the study of molecular evolution and genetic diversity. However, cpDNA of only a single Skeletonema species (S. pseudocostatum) has been constructed, hindering in-depth investigation on Skeletonema species. In this study, complete cpDNAs of five Skeletonema species were constructed with cpDNAs of four species S. marinoi, S. tropicum, S. costatum, and S. grevillea constructed for the first time. These cpDNAs had similar sizes and same numbers of genes. These cpDNAs were highly syntenic with no substantial expansions, contractions, or inversions. Interestingly, two copies of petF, which encodes ferredoxin with critical role in iron dependency, were found in all five Skeletonema species, with one copy in the cpDNA and another copy in the nuclear genome of each species. Selection analysis revealed that all PCGs of cpDNAs were undergoing purifying selection. Despite the high conservation of these cpDNAs, nine genomic regions with high sequence divergence were identified, which illustrated substantial variations that could be used as markers for phylogenetic inference and for tracking Skeletonema species in the field. Additionally, the numbers of simple sequence repeats varied among different cpDNAs, which were useful for detecting genetic polymorphisms. The divergence times estimated using PCGs of cpDNAs revealed that most of these species were established within ~33 Mya, consistent with that estimated using mtDNAs. Overall, the current study deepened our understanding about the molecular evolution of Skeletonema cpDNAs.